CARDIOTOCOGRAPHY IN THE DIAGNOSIS OF DISEASES FUNICULAR - Yanque Montufar, Ramiro (2015)
Paths of electronic monitoring of 153 pregnant women over 30 weeks pregnant, who were monitored in Unit Obstetric Physiology (UFO) of the Maternity Hospital of Lima, the Mother National Institute of Children (INAMI) were studied for the presence or of variable decelerations and after childbirth check for circular cord in the newborn, in order to establish the goodness of the diagnostic method. The presence of 6 twin pregnancies took a total of 159 RN. In 38 of the 159 cases (23.3%) were 1-2 circular umbilical cord around his neck or body. The negative predictive value and specificity of the monitoring were high (80.2% and 82.1% respectively). The positive predictive value (36.4%) and the sensitivity of the diagnostic method (32.4%) were lower for circular. Where there was no variable decelerations on paths, even in cases where there nuchal cord, Apgar in 96% of the RN was equal to or greater than 7 per minute of birth. It can be considered that the CTG is a method of high specificity to deny the existence of circular cord and negativity stressante test is not a good predictor of fetal welfare and RN.